Does ’Honeymoon Period’ Exist in Type 2 Diabetes Mellitus? - Ashrafuzzaman, SM; Latifd, Zafar A (Ibrahim Medical College Journal, 2009)
Temporary remission of type 1 diabetes mellitus (T1DM) occurs following initiation of insulin therapy. This period of temporary remission without insulin therapy is called ‘honeymoon period'. But no such temporary remission usually occurs in type 2 diabetes (T2DM). We report here two cases of type 2 diabetes mellitus where such honey moon period was observed. Ibrahim Med. Coll. J. 2008; 2(2): 67-69 Key words: Diabetes Mellitus doi: 10.3329/imcj.v2i2.2942